Microstructure evolution and mechanical properties of martensitic stainless bearing steels with different carbon nitrogen ratios - Yabo Wang; Hao Feng; Huabing Li; Yumeng Zhang; Zhouhua Jiang; Xiaodong Wang (Journal of Materials Research and Technology)
This study investigates the effect of adjusting the carbon nitrogen ratio on the microstructure and mechanical properties of martensitic stainless bearing steels, keeping the equivalent total carbon and nitrogen content. The results demonstrate that the sample with nearly equal weight percentages of C and N exhibits optimal comprehensive performance, achieving impressive yield strength, ultimate tensile strength, and uniform elongation of up to 1806.5 MPa, 2279.3 MPa, and 4.5%, respectively. Distinct phase ratios and morphologies observed across the three C/N ratios after identical heat treatment process suggest varying intrinsic mechanisms due to differences in C and N solid solubility in the matrix. The specimen with almost balanced C and N shows the highest interstitial atom solubility in the austenite phase, stabilizing austenite and lowering stacking fault energy. Abundant fine twins in martensite and stacking faults in austenite contribute to increased elongation without compromising strength. In contrast, specimen with higher N/C ratio exhibits numerous nitrides, limiting N atom solid solution in austenite during austenization, resulting in martensite with twins and dislocations. Specimen with higher C/N ratio shows extensive carbide precipitation and mainly dislocation-type martensite. The study deepens the understanding of C and N interactions in advanced bearing steels and provides a foundation for improving mechanical properties of such steels.